Valoración económica calidad del aire sector “San Alfonso” cantón Riobamba, provincia de Chimborazo, periodo 2023 - Lema Guevara, Frank Alexander (2024)
ABSTRACT The present investigation focuses on determining the availability of accepting economic compensation from the San Alfonso sector, Riobamba canton, Chimborazo province due to the contamination received by the company INCOREG S.A. In the period 2023, the Contingent Valuation Method (CVM) is used, which provides us the necessary tools that determine whether said population is willing to accept remuneration in monetary units and how much the economic item would be delivered to everyone (head of household) calculated in US dollars. This method is applied to a sample of the target population made up of 116 people through surveys which were applied using the computer tool forms, based on the key structuring of the questions, the minimum amount that said residents are willing to accept was determined, On the other hand, when obtaining the results of the application, they are tabulated and visually represented using pie charts, for greater reading comprehension, in this way the data obtained were applied to the LOGIT and PROBIT econometric models. Which allow determining the probability of acceptance of the compensation, among the various variables used, those that are significant are Age, Marital Status, Expenses due to health problems, Perception of air quality, Health problems, Monthly amount, Absence from Work, Change of home address, when carrying out this process it was obtained that both values were similar, during which it was necessary to apply the confusion matrix. In this analysis, it was determined that the optimal model is the LOGIT, showing greater significance compared to the PROBIT model. Having carried out this process, it is determined that the economic item willing to accept by the residents is 2.32 dollars, this value had a probability of acceptance of 99.99%. Considering this result, the respective discussions, deductions, conclusions, and recommendations necessary for this investigative work are carried out. Keywords: Pollution, Economic Compensation, LOGIT, Contingent Valuation Method, PROBIT, Remuneration. Firmado electrónicamente por: JHON JAIRO INCA GUERRERO Reviewed by: Msc. Jhon Inca Guerrero. ENGLISH PROFESSOR C.C. 0604136572